Pengaruh Rasio Keuangan Terhadap Harga Saham LQ45 Tahun 2020-2023 - Salsabila Nur Aini; Sjarief Hidajat (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study was conducted to examine the effect of Earnings per Share, Dividend per Share, Price to Earnings Ratio, Market to Book Ratio, and Economic Value Added on stock prices of companies included in the LQ45 index listed on the Indonesia Stock Exchange (IDX) for the period 2020–2023. The sample was selected using the purposive sampling method, resulting in a total of 24 selected companies. This research employed a quantitative method and used multiple linear regression analysis with the Ordinary Least Squares (OLS) method, processed using IBM SPSS Statistics 27 software. The findings indicate that Earnings per Share (EPS) has a positive and significant effect on stock prices, Dividend per Share (DPS) has a positive and significant effect on stock prices, Price to Earnings Ratio (PER) has a positive and significant effect on stock prices, Market to Book Ratio (MB) has no significant effect on stock prices, and Economic Value Added (EVA) has a negative and significant effect on stock prices. Collectively, the five independent variables significantly influence stock prices. The findings of this study are expected to serve as a reference for investors in making investment decisions.